When Visibility Matters: Short-Term Versus Long-Term Costs and Benefits of Visible and Invisible Support. (November 2013) - Girme, Yuthika U.; Overall, Nickola C.; Simpson, Jeffry A.
Sixty-one couples engaged in two video-recorded discussions in which one partner (the support recipient) discussed a personal goal with the other partner (the support provider). The support provider's visible and invisible support behaviors were coded by independent raters. Measures of perceived support, discussion success, and support recipients' distress during the discussion were gathered. Recipients also reported their goal achievement at 3-month intervals over the following year. Greater visible emotional support was associated with greater perceived support and discussion success for highly distressed recipients, but it was costly for nondistressed recipients who reported lower discussion success. In contrast, greater invisible emotional support was not associated with perceived support or discussion success, but it predicted greater goal achievement across time. These results advance our current understanding of support processes by indicating that the costs and benefits of visible support hinge on recipients' needs, whereas invisible support shapes recipients' long-term goal achievement.